(untitled) (World Economics and Finance Bulletin, 2025)
The article examines the procedure for organizing an audit in commercial banks based on international auditing standards (IAS). Using the example of the audit practice of large commercial banks of Uzbekistan (Asakabank, Milliy Bank, Xalq Bank, Ipak Yuli Bank), the procedure for the joint application of IAS 315, IAS 330, IAS 500, IAS 540, IAS 700 and IAS 701 standards in bank audits is revealed